EFISIENSI ALAT BERAT PADA PELEBARAN JALAN KOLONEL H. BARLIAN PALEMBANG - Kurniawan, Reffanda (JURNAL MEDIA TEKNIK, 2011)
ABSTRACTThe highway is the means of transportation that support the development and growth of a region. Some regions of Indonesia means the road could not be said to be well. Because of that, the Government of South Sumatra region, particularly the city of Palembang Government trying to build new roads. One of them is widening streets Kol. H. Barlian Palembang. Heavy equipment is one of the important factors in a construction project. Productivity efficiency use of heavyequipment on widening streets Kol. H. Barlian Palembang needed to optimize the use of your budget and time. Heavy equipment work production calculated on the basis of work and flexible tool at work, namely the foundation layer of aggregate class A, class B, the foundation layer of aggregate, AC-Base layer, layers and layers of AC-BC AC-WC, for rigid and road foundation layers, and is the surface layer. So it can be concluded that the activity of the foundation of aggregate class A and class B the delay does not occur.While on aggregate employment AC-WC, AC-BC and AC-Base was timely because the tools used in accordance with theplanned. An excess of heavy equipment on the project of widening streets Kol. H. Barlian of Palembang, on the type of dump trucks.